Development of Multi Representative Physics E-Module with the Materials of the Momentum and Impulse Grade X High School/Islamic High School Students - Ramadhan, Singgih Zein Massaid; Murtono (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2023)
The module is a teaching material that is packaged practically and systematically so that it can be accessed independently by both teachers and students. E-modules are adaptations of learning modules to the current digital era, so that in operation e-modules utilize technology, both computers and cellphones. This study aims to 1) produce multi-representation-based physics e-modules on momentum and impulse material that can be used in learning, 2) determine student responses related to multi-representation-based physics e-modules that have been produced, and 3) determine the quality of physics-based e-modules multi representation that will be used in classroom learning. This research belongs to R&D (Research and Development) research with the 4D Thiagarajan development model consisting of Defining, designing, Development, and Disseminating. This research is limited to the Development stage, to be precise, in extensive trials. The instruments used in this study included validation sheets, assessment sheets, and student response questionnaires. E-Modules are validated by material experts and media experts. The validation sheet in this study uses Aiken's V scale with three scales. In comparison, the e-module quality assessment was conducted by two material experts, two media experts, and two physics teachers. The e-module quality assessment sheet uses a Likert scale with four scales. The e-module trials in this study were divided into two stages: limited and extensive. Limited trials were conducted on ten students, while comprehensive trials were conducted on 36 students. Student response questionnaires used the Guttman scale with two scales: